2022
DOI: 10.3390/ijerph192013324
|View full text |Cite
|
Sign up to set email alerts
|

Source Analysis and Contamination Assessment of Potentially Toxic Element in Soil of Small Watershed in Mountainous Area of Southern Henan, China

Abstract: In this study, the concentrations of potentially toxic elements in 283 topsoil samples were determined. Håkanson toxicity response coefficient modified matter element extension model was introduced to evaluate the soil elements contamination, and the results were compared with the pollution index method. The sources and spatial distribution of soil elements were analyzed by the combination of the PMF model and IDW interpolation. The results are as follows, 1: The concentration distribution of potentially toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The traffic in the area is convenient. Zhangqiu District is located on the northern foot of Taiyi Mountain, bordering on the North China Plain [24]. The Great Wall Ridge stretches to the south, and Changbai Mountain stands to the east.…”
Section: Study Areamentioning
confidence: 99%
“…The traffic in the area is convenient. Zhangqiu District is located on the northern foot of Taiyi Mountain, bordering on the North China Plain [24]. The Great Wall Ridge stretches to the south, and Changbai Mountain stands to the east.…”
Section: Study Areamentioning
confidence: 99%
“…Cheng et al [ 36 ] studied the cultivated soils of Henan Province, with moderate and moderate-to-strong contamination from Mn and Zn. In a soil sample from a small watershed in the mountainous area of southern Henan, China, 68.55% of the topsoil in the study area was clean, with Hg found to be the main contamination element [ 37 ]. Previous research has demonstrated a positive correlation between the total Cd content in soil and the concentration of Cd in wheat grain near mining areas and plants [ 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%